Nesting Biology of Euglossa dodsoni Moure (Hymenoptera: Euglossinae) in Panama (2009)
The orchid bee genus Euglossa contains more than 100 species distributed throughout the Neotropics from Paraguay to Mexico (Michener, 2000). Most species nest in protected cavities such as in logs, trunks, small cavities between rocks, and man-made constructions, but some species build their nests in exposed sites where they are attached to small branches or underneath leaves (Eberhard, 1988; Nemesio, 2006). Nest of many species are made of wax and resins mixed with plant material and other materials, creating a strong structure that provides protection against environmental fluctuations and predators (Roubik and Hanson, 2004). Most Euglossa females are solitary nesters, but multifemale nesting is facultative for some species (Soucy et al., 2003; Augusto and Garofalo, 2004). In E. hyacinthina, for example, all females that cohabit in a nest are capable or reproducing and there are no clear indications of dominance among the individuals, with sex ratios biased toward females (Soucy et al., 2003; Capaldi et al., 2007). Euglossa dodsoni Moure is a small orchid bee known from cloud forests in Costa Rica and Panama (Ramirez et al., 2002), but otherwise little is known of its biology. Dodson (1966) described several aspects of its nesting biology based on a population found in Costa Rica. Here, we describe the nesting biology from a small population in western Panama, including information on external and internal nest architecture, contents and sex ratios.